2021
DOI: 10.1186/s12891-021-04307-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple intravenous tranexamic acid doses in total knee arthroplasty in patients with rheumatoid arthritis: a randomized controlled study

Abstract: Background We aimed to determine the efficacy and safety of multiple doses of intravenous tranexamic acid (IV-TXA) on perioperative blood loss in patients with rheumatoid arthritis (RA) who had undergone primary unilateral total knee arthroplasty (TKA). Methods For this single-center, single-blind randomized controlled clinical trial, 10 male and 87 female participants with RA, aged 50–75 years, who underwent unilateral primary TKA were recruited. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…A very few studies tried to explore whether TXA would decrease perioperative blood loss and whether TXA would add the risk of related complications in patients with RA following TKA [ 23 , 24 , 31 ]. A randomized controlled trail conducted by Kang et al showed that three doses of postoperative TXA further decreased TBL and HBL without increasing the incidence of adverse events in RA patients following primary TKA [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A very few studies tried to explore whether TXA would decrease perioperative blood loss and whether TXA would add the risk of related complications in patients with RA following TKA [ 23 , 24 , 31 ]. A randomized controlled trail conducted by Kang et al showed that three doses of postoperative TXA further decreased TBL and HBL without increasing the incidence of adverse events in RA patients following primary TKA [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A very few studies tried to explore whether TXA would decrease perioperative blood loss and whether TXA would add the risk of related complications in patients with RA following TKA [ 23 , 24 , 31 ]. A randomized controlled trail conducted by Kang et al showed that three doses of postoperative TXA further decreased TBL and HBL without increasing the incidence of adverse events in RA patients following primary TKA [ 23 ]. Another study performed by Lei et al found that TXA use prior to surgery could dramatically diminish blood loss and transfusion requirement, decrease LOS and hospitalization expenses in patients with RA following primary TKA, without increasing the risk of complications [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the National Joint Registry, more than 100,000 knee replacements are performed each year in England, Wales and Northern Ireland. Whilst most studies related to the use of TXA in knee surgery have examined blood loss in patients with osteoarthritis, it has proven to be efficacious in patients with rheumatoid arthritis [6], cancer [7] and in revision surgery [8]. Therefore, it seems reasonable to administer TXA to all patients requiring knee arthroplasty, irrespective of their underlying diagnosis.…”
Section: Safety Datamentioning
confidence: 99%
“…However, the optimal regimen for TXA infusion remains undetermined. For example, there are conflicting results regarding the effect of multiple and higher doses on blood loss reduction [13][14][15][16]. The impact of differential regimens, such as continuous infusion or single bolus; timing of administration; and route of administration require further evaluation.…”
Section: Introductionmentioning
confidence: 99%